Surgical Correction of Whistle Deformity Using Cross-Muscle Flap in Secondary Cleft Lip - Choi, Woo Young (The Korean Society of Plastic and Reconstructive Surgeons, 2012)
BACKGROUND: The whistle deformity is one of the common sequelae of secondary cleft lip deformities. Santos reported using a crossed-denuded flap for primary cleft lip repair to prevent a vermilion notching. The authors modified this technique to correct the whistle deformity, calling their version the cross-muscle flap. METHODS: From May 2005 to January 2011, 14 secondary unilateral cleft lip patients were treated. All suffered from a whistle deformity, which is characterized by the deficiency of the central tubercle, notching in the upper lip, and bulging on the lateral segment. The mean age of the patients was 13.8 years and the mean follow-up period was 21.8 weeks. After elevation from the lateral vermilion and medial tubercle, two muscle flaps were crossed and turned over. The authors measured the three vertical heights and compared the two height ratios before and after surgery for evaluation of the postoperative results. RESULTS: None of the patients had any notable complications and the whistle deformity was corrected in all cases. The vertical height ratios at the midline on the upper lip and the affected Cupid's bow point were increased (P<0.05). The motion of the upper lip was acceptable. CONCLUSIONS: A cross muscle flap is simple and it leaves a minimal scar on the lip. We were able to reconstruct the whistle deformity in secondary unilateral cleft lip patients with a single state procedure using a cross-muscle flap.